Consumer Tribes in Tourism Contemporary Perspectives on Special-Interest Tourism - Pforr, Christof; Dowling, Ross; Volgger, Michael (Springer Nature Singapore : Imprint: Springer, 2021)
XIV, 268 p. 55 illus., 40 illus. in color.